Selection for Tolerance to Low Temperature-Induced Spikelet Sterility At Anthesis in Rice - Khan, D.R.; Mackill, D.J.; Vergara, B.S. (Wiley, 1986)
Low temperature stress is a major constraint to adoption of modern rice (Oryza sativa L.) cultivars in many temperate and tropical rice growing areas. Spikelet sterility induced at the reproductive stage is the most damaging effect of low temperature. The inheritance of tolerance for low temperature at anthesis was studied in four indica (tropical) rice cultivars. The F1, F2, and F2‐derived F3 families of crosses between cold tolerant and cold susceptible parents were used. Individual plants were grown in small pots in the glasshouse room of the phytotron at the International Rice Research Institute, Los Baños, Philippines. Cold tolerance was measured as percent spikelet fertility of plants subjected to low day/night temperatures (20/20°C or 21/21°C) for 5 days at anthesis in the phytotron. Cold tolerance was usually associated with a higher number of pollen grains shed on the stigma. A continuous, unimodal distribution for the F2 populations suggested polygenic inheritance. The realized heritability based on response to selection ranged from 0.35 to 0.45. The results showed that it should not be difficult to recover cold tolerant progeny in crosses between tolerant and susceptible indica rices. Selection based on spikelet fertility in the F2 generation should give a marked response.